Biostimulant Activity of Sargassum sp. Extracts on Early Growth of Zea mays L. and the Phytohormones Content Analysis - Fauziatul Fitriyah; Muhammad Abdul Aziz; Sri Wahyuni; Hana Fadila; Insyiah Meida Luktyansyah; Sulastri Sulastri; Priyono Priyono; Siswanto Siswanto (Universitas Gadjah Mada, 2022)
Seaweed has been gaining global interest in agriculture for the development of marine-based plant biostimulants. This research aimed to study the effect of three different liquid extracts of Sargassum sp., acidic, alkaline, and water extract, on the germination and early growth of maize and to evaluate the phytohormones content responsible for the growth. Phytohormones content including Indole-3-acetic acid (IAA), gibberellins (GA), kinetin and zeatin were analyzed using high-performance liquid chromatography (HPLC) and bioassay was performed twice on maize. Parameters observed on the bioassay were germination percentage, number of roots, shoot length, shoot weight and root weight under 4 different concentrations with 0.5; 1.5; 3.5; and 5% in the first bioassay and 3.5% concentration in the second bioassay. Both bioassays following randomized complete design and the data were analyzed using one-way ANOVA using post hoc test of Duncan Multiple Range Test (DMRT) at error probability of 5% in Genestat software. Phytohormones content in the seaweed extract indicated that alkaline extract was rich in IAA, gibberellin, and zeatin content, while water extract showed the highest kinetin content. The first bioassay indicated that lower concentration of the seaweed extracts gave better growth in all extracts, therefore a 3.5% concentration was chosen for the second bioassay with higher replication for each treatment. The second bioassay confirmed alkaline extract resulted in the highest germination while the highest seedling height, number of roots, shoot and root weight were resulted from acidic extract treatment. In conclusion, Sargassum sp. extracts obtained from acidic, alkaline, and water-based extraction methods, were able to improve the shoot and root growth of maize plants. The acidic extract showed the highest growth promotion among other extracts with the lowest phytohormones content.